Magnetic field measurement with applications to modern power grids - Huang, Qi 1976-; Khawaja, Arsalan Habib; Chen, Yafeng; Li, Jian (Wiley, 2020)
A comprehensive review of the development, challenges and utilisation of magnetic field measurement Magnetic Field Measurement with Applications to Modern Power Grids offers an authoritative review of the development of magnetic field measurement and the application of the technology to the smart grid. The authors, noted experts in the field, present the challenges to the field of magnetics and explore the use of cutting-edge magnetic technology in the development of the smart grid. In addition, the authors discuss the applications of magnetic field measurements in substations, generation systems, transmission systems and distribution systems. The specialized applications of magnetic field measurements in these venues are explored, including the typical sensors used, the field strength levels and spectral frequencies involved and the mathematics that are needed to process data measurements. The book presents the complex topic of electromagnetics in clear and understandable terms.